Randomized trial comparing episiotomies with Braun-Stadler episiotomy scissors and EPISCISSORS-60® - Sawant G (Dove Medical Press, 2015)
Ganpat Sawant, Divya Kumar Dr DY Patil Medical College and Hospital, Nerul, Navi Mumbai, India Introduction: Episiotomy angle is a crucial factor in causation of obstetric anal sphincter injuries (OASIS), which are the major cause of female bowel incontinence. Sutured episiotomies angled too close to the midline (<30 degree) or too far away from the midline (.60 degree) fail to unload the perineum sufficiently and predispose to OASIS. A 25-degree post-delivery episiotomy suture angle has a 10% risk of OASIS while 45-degree episiotomy is associated with 0.5% risk. To account for perineal distension at crowning, a 60-degree episiotomy incision is required to achieve 43–50 degree suture angles. We compared episiotomy suture angles with commonly used Braun-Stadler episiotomy scissors with the new fixed angle EPISCISSORS-60®. Methods: Ethical approval was obtained. A prospective cluster randomization design was chosen. Thirty-one patients were required in each group for a 12-degree difference with power at 90% and 5% significance. Sutured episiotomy angles and post-delivery linear distance from caudal end of the sutured episiotomy to the anus were measured with protractors and rulers. Two-tailed t-tests were used to compare the two groups. Results: Thirty-one nulliparae had episiotomies with EPISCISSORS-60®, 32 with Braun-Stadler. Mean age (25 versus 24.8 years) was similar. EPISCISSORS-60® episiotomies were angled 12 degrees more laterally away from the anus compared to Braun-Stadler (40.6 degrees, 95% confidence interval [CI] ±2, interquartile range [IQR] 35–45 versus 28.3 degrees, 95% CI ±2, IQR 25–30, P<0.0001). The post-delivery linear distance from caudal end of the sutured episiotomy to the anus was 15 mm more with the EPISCISSORS-60® compared to Braun-Stadler (35 mm, 95% CI ±2.2, IQR =30–39 versus 19.5; 95% CI ±1.3, IQR =14.75–22.25 P<0.0001). EPISCISSORS-60® episiotomies measured longer (47 mm versus 40 mm, P<0.0001). There were no OASIS cases in the EPISCISSORS-60® group versus one in the Braun-Stadler group. Conclusion: The EPISCISSORS-60® sutured episiotomies are much further away from the midline in angular and distance measures, hence at lower OASIS risk. Keywords: episiotomy, EPISCISSORS-60®, obstetric anal sphincter injuries (OASIS), perineal tears